1984
DOI: 10.3109/13816818409006122
|View full text |Cite
|
Sign up to set email alerts
|

Immune complexes in retinitis pigmentosa

Abstract: SUMMARY In a group of 46 patients with retinitis pigmentosa (RP) we studied the presence of circulating immune complexes (CIC) and the alterations in the complement system. Our results showed the presence of CIC in 43.5% of the patients studied, reduced levels of the complement components C3 and C4 (p<0-001), and of the haemolytic activity CH50 (p<0-001) when compared with a control group consisting of a 100 healthy subjects. We found a statistically significant correlation between the values of C3 and CIC (p<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Recent studies by Kyger et al, has shown the presence of pathogenic auto-antibodies and T cell activation against retinal antigens in Royal College of Surgeons (RCS) rats [ 23 ]. Further, the presence of retinal auto-antibodies in RP patient’s blood has been reported [ 24 ]. Since the generation of IgG [ 25 ] producing B cells requires antigen specific T cell activation [ 26 ], the nature T cell response is of keen interest.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by Kyger et al, has shown the presence of pathogenic auto-antibodies and T cell activation against retinal antigens in Royal College of Surgeons (RCS) rats [ 23 ]. Further, the presence of retinal auto-antibodies in RP patient’s blood has been reported [ 24 ]. Since the generation of IgG [ 25 ] producing B cells requires antigen specific T cell activation [ 26 ], the nature T cell response is of keen interest.…”
Section: Discussionmentioning
confidence: 99%